On Karolis Čižauskas’s Doctoral Thesis “Nobility and Lordship in the Grand Duchy of Lithuania from the Late 15th to Early 17th Centuries: Discourse and Social Relations”, and its Defense - Račickas, Ignas (Lietuvos istorijos studijos, 2025)
-